Malaysian corporate finance and governance behavior - Fauzias Mat Nor; Ruzita Abdul Rahim; Norazlan Alias; Mohd Hasimi Yaacob (Penerbit Universiti Kebangsaan Malaysia, 2012)
This study analyzes the performance of 361 non-financial public firms that are listed on Bursa Malaysia during a relatively tranquil period from 2002 until 2007. The objective is to identify the corporate finance and governance practices that contribute to firm performance. In this study, performance is measured using Tobin's Q. The results from a fixed-effect panel data regression on 2166 yearly-firm observations show four significant explanatory factors; leverage, dividend per, CEO duality and board size.The result imply that firms are more likely to perform if they employ more debt, pay higher dividend per share, hire different individuals to assume the two most important roles in the company and maintain a smaller number of directors. The four factors are then used to construct a model in which viability is proven if it can effectively differentiate the financial and governance characteristics of the high performers from the poor performers.The model seems more effective in predicting high performance, rather than low performance.High performance companies are therefore those that pay a much higher divided per share and separate the roles of CEO and Boards Chair. Dept ratio and Board size are less definitive in segregating the two groups of companies.